GEOTECHNICAL ASSESSMENT OF RESIDUAL CLAY IN ZARIAGI, LOKOJA, NORTH-CENTRAL NIGERIA: IMPLICATION FOR INDUSTRIAL APPLICATIONS: Implication for industrial applications (FUDMA JOURNAL OF SCIENCES, 2024)
Clay is one of the world's most important and oldest building materials but also poses some challenges for civil and geotechnical engineers. Hence, understanding its geotechnical properties is key to the determination of their industrial applications. The geotechnical characteristics of six residual clay samples from the crystalline basement rocks in Zariagi, Lokoja, north-central Nigeria, were evaluated to determine its suitability for construction and civil engineering. Parameters assessed included particle size distribution, consolidation, specific gravity, Atterberg limits, linear shrinkage, loss on ignition, compaction, and permeability. Grain size analysis and Atterberg limit tests classified the samples as clayey. Liquid limit ranged from 36% to 37%, indicating low plasticity. The plastic limit ranged from 33.38% to 34.66%, and the plasticity index from 2.14% to 2.71%, suggesting the clay exhibits low to medium swelling potential when wet and can withstand volumetric shrinkage when dry, meeting the requirements for barrier soils. Compaction tests revealed an optimum moisture content (OMC) of 14.90% to 18.50% and maximum dry density (MDD) of 1270 kg/m³ to 1320 kg/m³, indicating suitability for building construction. Linear shrinkage percentages ranged from 2.86% to 4.29%, indicating moderate linear and low volumetric shrinkage. Loss on ignition values from 3.74% to 4.49% suggested low organic matter content and the absence of swelling clays. Permeability values ranged from 0.000133 cm/sec to 0.000140 cm/sec, suggest moderate permeability. The results suggest the Zariagi clay is suitable for barrier soil and building construction applications.
Keywords: Residual clay; Geotechnical assessment; Lokoja; North-central Nigeria